Serum Antibacterial Activity Test of Chinese Betel Extract (Peperomia Pellucida) Against Staphylococcus Aureus Bacteria - Asri Satrianingrum; Gigih Kenanga Sari; Mingle A Pistanty (Yayasan Citra Dharma Cindekia, 2023)
Chinese betel is a weed plant that contains antibacterial compounds such as flavonoids, saponins, tannins, triterpenoids and alkaloids which are used as acne treatment therapy. The aim of the research is to obtain a serum with good inhibitory power from varying concentrations of 5%, 10% and 15%. , then a stability evaluation was carried out including organoleptic tests, homogeneity, pH, viscosity, spreadability and stickiness as well as testing for antibacterial activity against the growth of Staphyloccocus aureus. Data analysis was carried out using One-Way ANOVA. The results obtained from the stability test have good standards for organoleptics, homogeneity, pH, viscosity, spreadability and adhesion. Antibacterial testing showed that the diameter of the inhibition zone formed against Staphyloccocus aureus bacteria was 15.71 mm, 18.94 mm and 23.06 mm. Based on the results obtained, Chinese betel serum has good stability and all formulas can inhibit the growth of the acne-causing bacteria Staphyloccocus aureus as evidenced by the diameter of the inhibition zone formed which is in the very strong category